If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + -8 = 10 + -1b Reorder the terms: -8 + 4b = 10 + -1b Solving -8 + 4b = 10 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. -8 + 4b + b = 10 + -1b + b Combine like terms: 4b + b = 5b -8 + 5b = 10 + -1b + b Combine like terms: -1b + b = 0 -8 + 5b = 10 + 0 -8 + 5b = 10 Add '8' to each side of the equation. -8 + 8 + 5b = 10 + 8 Combine like terms: -8 + 8 = 0 0 + 5b = 10 + 8 5b = 10 + 8 Combine like terms: 10 + 8 = 18 5b = 18 Divide each side by '5'. b = 3.6 Simplifying b = 3.6
| x^4+8x^2+15=0 | | 4(h+1)=2(5h+6) | | 8x^5-25y^3+80x^4-x^2y^2+20x^3-10xy^3=0 | | 6x+27=13x-57 | | 6x+4x+4+9=7x+3+2x | | 8(x+1)=9+8x | | [a-3]-14=-6 | | 4x+4-1=-9x+7 | | 3ax-2=5bx+7 | | 10x+4+3+6=7x+3+6x | | 7(x+9)=4[x-(6-x)] | | 3(x-3)+16=2(x+5) | | 6x+6= | | 10x+2+4x+7=13x+3 | | 12y-9=16y+19 | | 9x-3=3+8x | | 7x+3y=16 | | 23-6x=-61 | | v(4v-24)=-6 | | -8y+5=-9y+3 | | h^2+26h-10=0 | | -6y+4=7y+5 | | 27x+13x=73 | | 3x^2-3x+5=0 | | 5p+5=7-4p | | x-2x+5=5 | | X^2+11x+13=0 | | (3x+7)(x+1)=10 | | 9-41= | | x^2-30x+125=0 | | 2x(x+8)+15=0 | | g^2-8g+11=0 |